Problematika Hukum dalam Pengelolaan Dana Desa berdasarkan Perspektif Otonomi Desa di Lampung (Studi Desa Paku Negara Kabupaten Pesisir Barat) - Dauri Dauri; Thio Haikal Anugerah; Hanifah Nuraini (Universitas Medan Area, 2020)
The birth of village autonomy has made the village more independent in taking care of the household in the village. With the promulgation of Law Number 6 of 2014 concerning Villages, the Domestic Metric Regulation Number 20 of 2018 concerning Village Financial Management makes village governments have their own autonomous bodies to manage village finances. Roles and responsibilities received by villages have not been matched with adequate Human Resources (HR) in terms of both quantity and quality. Even though the funds owned by a village are very large, but if they are not properly regulated in their planning and users, it will result in these funds being wasted or unable to provide maximum results in the use of these village funds. At present Indonesia Corruption Watch (ICW) many Village Officers, especially the Village Head, are affected by Hand Tagging Operations (OTT) by the Corruption Eradication Commission (KPK). The problem that will be discussed in this study is how the legal problems in the preparation of the Village Budget (APBDes) for village development and what are the inhibiting factors in implementing the APBDes preparation. The method used is normative legal research and empirical legal research. The results showed that, the legal problems in the preparation of APBDes went through 3 (three) stages, namely the preparation, evaluation and determination stages. However, in the preparation stage of the APBDes preparation process, it did not directly involve the community as stipulated in the legislation related to village financial management. the inhibiting factors of the Village apparatus and Village Association Institutions lack understanding of the Village Law and its implementing regulations, weak planning ability.